(untitled) (Global Journal of Human-Social Science, 2012)
The paper investigates the effectiveness of organisational training for the job market It seeks to find how training influences where and when people work in terms of type scale geographical spread of the business the skills required for the purpose of training significance and dependence access and analyse how professional training is planned and organised for the benefit and demands of the organisation how training relates business aims as influenced by appraisals career development recruitment information dissemination connection with experts use and development of resources and skills These form the bases for the six research questions The paper delimits professional training to the training that takes place in the tertiary institutions in Nigeria and the job market includes all sectors of the Nigerian economy that can offer employment Literature is reviewed based on Bloom s theory and the Kirkpatrick model Using the descriptive survey design the study explores how professional training in the formal sector influences the job market